The Transpersonal Dimension of Spirituality: Transcending Through Art, a Historical View - Diego Pedro, Rebeca (2020)
Spirituality is present in a nuclear way in the life of people offering a union between each of the components of their daily lives. The transpersonal dimension of Spirituality allows the person to connect with something that goes beyond themselves. In this aspect, art has been one of the main vehicles throughout history that humanity has used to transcend. The present work focuses on making a historical journey through the artistic manifestations of the first communities attending to the links between art and spirituality. Through the analysis of the first historical periods and their works of art, it will be possible to contemplate how Spirituality has been present in humanity since its origins being a dynamic phenomenon and, the way in which art, has allowed that personal transcendence of each individual with himself, with a superior being or by connecting with the other present and future members of his community.